Pengaruh Pemberian Jus Semangka (Citrullus vulgaris Schard.) Peroral Terhadap Jumlah Spermatozoa Mencit (Mus musculus) Yang Dipapar Asap Rokok - Lusy Elwinda; Rina Amtarina; M.Yulis Hamidy (Fakultas Kedokteran Universitas Riau, 2011)
Infertility is influenced by many factors, one of them is reactive oxygen species (ROS) containing free radicals. Freeradicals can be neutralized by antioxidants. Watermelon (Citrullus vulgaris Schard.) contains compounds with strongantioxidant activity so that protect the spermatozoa from the toxic effects of ROS. The purpose of this research was todetermine the effect of watermelon juice to the number of spermatozoa’s mice exposed by cigarette smoke. Its designwas the post test only, while the subjects were 20 male mices, which divided into five groups were baseline, K(-), P1,P2 and P3. This experimental study lasted for 14 days. On the 15th day, all mice were terminated and the number ofspermatozoa was examinated. One way anova test showed significant differences of spermatozoa count between groups(p=0,000). Based on post hoc test there were significant differences between group of baseline with K(-) and P1,between group of K(-) with P2 and P3, and between group of P2 with P1 and P3. This study showed that watermelonjuice increased the number of spermatozoa in mice exposed by cigarette smoke and dose 0.32 ml/day gave the besteffect.